SISTEM INFORMASI ONLINE SHOP LABKARA BERBASIS WEB (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
The web-based online shop Labkara Information System is an application designed to make it easier for customers to place orders for goods and assist owners in recording and managing customer ordering data better. The process of ordering goods at the Labkara online shop still uses the manual method, namely, customers place orders for products by sending messages through social media applications, and managing order data is done by recording it via Google Sheets. This causes an inefficient ordering process at the Labkara online shop. The web-based online shop Labkara Information System has a feature to display product information, which includes names, photos, and prices. In making this application, the Waterfall System Development Life Cycle (SDLC) development methodology is used, which consists of analysis, design, implementation, testing, and maintenance. The database in this application is supported by the MySQL database that is in XAMPP. PHP and HTML are programming languages used to create programs, resulting in a website application that can assist assist Labkara online shop administrator in data processing and makes it easier for customers in placing product orders.